Kajian Perencanaan dan Pembangunan Sistem Informasi Berbasis WebGIS Kota Palu - Ghefra Rizkan Gaffara; Ken Martina Kasikoen; Gabriella Trisna Yudhanti; Fina Zaimah Maznah (Information Technology and Science(ITScience), 2023)
Palu is located in the Sulawesi most active fault, with an annual movement of about 7 cm. The epicenter was located near Donggala, with tremors felt in various regions, including North and East Kalimantan. The earthquake had an energy release of approximately 2.5 × 10^20 Nm, equivalent to 200 times the power of the Hiroshima bombing. This presents an interesting subject for studying how to develop a good and accessible disaster mitigation system by utilizing the available information technology today, where disaster information can be easily accessed and synchronized with existing disaster management systems to reduce the impact of earthquake disasters. This research aims to analyze earthquake disaster risks and develop a mitigation model through a spatial analysis approach using Geographic Information System (GIS). The methods employed include analyzing disaster risks by utilizing Digital Elevation Model (DEM) data, road data, and overlaying images with earthquake damage distribution. Additionally, qualitative analysis in the form of disaster management and mitigation analysis is conducted. The data obtained is used to design evacuation routes and determine post-earthquake shelter locations. The results of this research provide a better understanding of disaster vulnerability in the studied areas. Through the developed mitigation model, this research contributes to identifying effective mitigation strategies. The designed evacuation routes and post-earthquake shelter locations provide crucial information for emergency response planning. Furthermore, the analysis results are presented in the form of a WebGIS accessible through a website, enabling easy access to information by the general public